PERBANDINGAN PENJADWALAN PROYEK ANTARA METODE KONVENSIONAL DENGAN APLIKASI MICROSOFT PROJECT (STUDI KASUS: PEMBANGUNAN GEDUNG DUA LANTAI SDN 1 PEDUNGAN) - SUNATHA, I GEDE NGURAH; PRAGANINGRUM, TJOKORDA ISTRI; NADA, I MADE; DWIYANTI, NI MADE MEILAN FLORENZIA (Universitas Mahasaraswati K. Mataram, 2024)
Good construction project implementation is obtained from good and detailed management. The success of project management is supported by a detailed and thorough planning and scheduling method. Project scheduling has many types with various forms, advantages and disadvantages, even in current technological developments, applications are available that can help plan, implement and control projects, namely the Microsoft Project application. In the implementation of the SDN 1 Pedungan Two-Floor Building Development project, it still uses scheduling using the conventional method (S-Curve). With the existence of various forms of scheduling, this writer compares the method between the S Curve and the Critical Path Method (CPM) to obtain effective and efficient scheduling. The data used in this study are quantitative data such as the Budget Plan (RAB) which produces job descriptions and volumes, the Time Schedule plan which produces the activity duration of each work item, the predecessor and project start time, the analysis list which produces resource requirements and the calendar. workflow that returns project start time, workdays, workhours, worktime and holidays. After comparing the duration of each work between the conventional method using the Microsoft Project 2019 application in the construction project of the Two-Floor Building at SDN 1 Pedungan, the implementation time plan is faster than the conventional method, namely with a difference of 31 days, this is influenced by calculations of needs and availability of resources. power (Unit Max) per day adjusted to the volume of work